Comparing multi-level and full spectrum detention design for urban stormwater detention facilities - Zhang, Xiaoju, author; Roesner, Larry A., advisor; Willson, Bryan D., advisor; Grigg, Neil S., committee member; Kampf, Stephanie, committee member (Colorado State University. Libraries, 2010)
Peak flow attenuation and water quality control are widely used in urban stormwater systems. Standard practice typically involves peak shaving of post-development flows to pre-development peak flow levels to control flood flows and best management practices (BMPs) for removing pollutants from runoff. Usually both practices are integrated by using Multi-level Detention ponds. Recently, Wulliman and Urbonas (2005 and 2007) have proposed the so-called Full Spectrum Detention approach to design detention facilities able to control runoff events. This method is based on the concept of capturing the Excess Urban Runoff Volume (EURV) that results from urbanization and releasing it over a period of 72 hours. This method has been tested successfully for the Denver region and excellent matching of post-development peak flows to pre-development peak flows has been achieved. However, these results have been obtained using discrete design storms and the model has not been studied using a continuous simulation approach. Continuous simulations are useful because they provide information about the long-term performance through peak flow exceedance frequency and flow duration curves. Moreover, these results can be used to define the stream erosion potential, a metric that characterizes the geomorphic stability of urban streams. Continuous simulation has been successfully used to characterize the performance of Multi-level Detention method, which uses combined peak shaving and extended detention practices, and protocols to reduce urbanization impacts in different locations have been demonstrated with it. This study compares the effectiveness and differences of the Multi-level Detention design approach with that of the Full Spectrum Detention approach through the use of design storms and 60-year continuous precipitation records in a conceptual watershed for two different climate regions in the United States. The US EPA Stormwater Management Model (SWMM) is used to simulate the response of a conceptual watershed using both design approaches. Sensitivity analysis of the land-use properties is performed in order to validate the assumptions of the Full Spectrum Detention method by using both Colorado Unit Hydrograph Procedure (CUHP) and SWMM models. The performances of these two design approaches are tested initially by comparing the post-development peak flows for different design storms with the pre-development conditions. Additionally, 60 years of hourly rainfall records are used to run continuous simulations and compute peak flow frequency exceedance curves, flow duration curves, the hydrologic metrics T0.5, and average boundary shear stress curves, which are used to compute the stream erosion potential. The differences of both design methods are assessed by comparing the post-development results with those obtained for the pre-development conditions.
Department Head: Luis A. Garcia.